Glaciomarine Oceanographic and Suspended Sediment Dynamics, Kongsbreen system, Svalbard, 2010 - Hannah Marshburn; Ross Powell; Julie Brigham-Grette (Arctic Data Center, 2013)
Quantifying estuarine circulation and the resulting sediment dynamics of tidewater glaciers is crucial to developing an understanding of these dynamic systems, and their response to climate and sea level change. This study characterizes oceanographic conditions and suspended sediment loads resulting from glacial meltwater in proximal distance to the glacier terminus of the Kronebreen-Kongsvegen system, Kongsfjorden, Svalbard as a component of the Svalbard REU project. The study was conducted during July and early August of 2009, coinciding with maximum melt water volumes induced by elevated summer temperatures, and approaching the spring tidal maximum. Major fjord, oceanic, and glacial- induced brackish meltwater plumes were identified and evaluated for suspended particulate load through CTD scans, optical back scatter (OBS) readings, and water samples taken in perpendicular transects roughly 200-1000 m from the glacial termini. Sub-glacial upwelling systems on opposing sides of the glacial face were targeted for analysis and comparison. The control of tidal fluxes¬¬¬ on sediment and interflow mixing was examined. The fjord is an example of a system with active marine glaciers transitioning to terrestrial systems, vulnerable to circulation changes. The estuary consists of a three layer stratified system. A turbid shallow estuarine brackish mixing layer was identified, with temperatures ranging between 3-4oCelsius and practical salinity ranging from 15 to 31, a result of glacial outwash. An intermediate Atlantic interflow was identified through a warm saline water tongue at depths of 15-20 meters, with mean temperatures between 4-5o Celsius and salinity of 31 to 32. The fjord bottom water was characterized by a drastic temperature decrease at 30 meters from 5 to 1.2o Celsius over a 10-20 meter interval, with salinity constant at 33-34. Suspended particulate loads from water samples and OBS values were higher in the unrestricted sub-glacial upwelling plume system as opposed to the system in the semi-enclosed delta. The surface mixed layer contained the highest suspended particulate matter, with a mean sediment concentration of 0 .1351 kg/m3, compared to the intermediate and bottom water values of 0.06801 and 0.04376 kg/m3, respectively. Data during ebb tide phases indicate reduced water column stratification. Fjord waters and currents are strongly driven by thermohaline convection cycles due to their partial enclosure and protection from open ocean winds and waves. Research characterizing density driven mixing properties of inner fjord basin water columns is limited. Data generated in this study can be used to investigate the effects of glacial outwash, comprised of freshwater and sediment, on fjord circulation. Understanding how glacial meltwater is exported from fjords and interacts with ocean-climate systems is critical to hypothesizing future climate behavior.